Learning to Be an Orangutan—Implications of Life History for Orangutan Rehabilitation - Signe Preuschoft; Ishak Yassir; Asti Iryanti Putri; Nur Aoliya; Erma Yuliani; Siti Nur Badriyah; Paloma Corbi; Yoyok Sugianto; Bina Swastas Sitepu; Mukhlisi; Elfriede Kalcher-Sommersguter (Animals, 2021)
Orangutans depend on social learning for the acquisition of survival skills. The development of skills is not usually assessed in rescued orphans’ pre-release. We collected data of seven orphans over an 18-months-period to monitor the progress of ontogenetic changes. The orphans, 1.5–9 years old, were immersed in a natural forest environment with human surrogate mothers and other orphans. Social interactions deviated significantly from those of wild mother-reared immatures. Infants spent more time playing socially with peers, at the expense of resting and solitary play. Infants were also more often and at an earlier age distant from their human surrogate mothers than wild immatures are from their biological mothers. We found important changes towards an orangutan-typical lifestyle in 4- to 7-year-old orphans, corresponding to the weaning age in maternally reared immatures. The older orphans spent less time interacting with human surrogate mothers or peers, started to use the canopy more than lower forest strata and began to sleep in nests in the forest. Their time budgets resembled those of wild adults. In conclusion, juvenile orphans can develop capacities that qualify them as candidates for release back into natural habitat when protected from humanising influences and immersed in a species-typical environment.